Improving the material sustainability of strain-hardening magnesium-silicate-hydrate composite by incorporating aggregates - Kumar, Dhanendra (2024)
The existing strain-hardening magnesium-silicate-hydrate composites (SHMSHCs) utilize a magnesium-silicate-hydrate (MSH) paste-based cementitious matrix, using significant binder content, thus prone to higher embodied energy and carbon footprint. In this study, authors have explored the feasibility of incorporating aggregates without compromising the mechanical performance to improve the material sustainability of SHMSHCs. For this purpose, SHMSHCs utilizing microsilica sand and river sand with a median particle size of 0.18 mm and 1.10 mm, at varying sand-to-MgO weight ratios from 0 to 1.60, were experimentally investigated. The compressive strength of the SHMSHC was increased with the addition of aggregates. The initial cracking strength of the MSH cementitious matrix also increased with the addition of aggregates. All the SHMSHCs with microsilica sand and river sand showed strain-hardening behavior. The SHMSHCs with river sand demonstrated higher tensile strain capacity than microsilica sand SHMSHCs, whereas the effect on the ultimate tensile strength was the opposite. The residual crack widths of the SHMSHCs increased with the addition of aggregates. The beneficial effect of aggregate incorporation was reflected in the lower embodied carbon and energy in the SHMSHCs.